"NETtling" the host: Breaking of tolerance in chronic inflammation and chronic infection. (March 2018) - Skopelja-Gardner, Sladjana; Jones, Jonathan D.; Rigby, William F.C.
Abstract: How and why we break tolerance to self-proteins still remains a largely unanswered question. Neutrophils have been identified as a rich source of autoantigens in a wide array of autoimmune diseases that arise as a consequence of different environmental and genetic factors, e.g. rheumatoid arthritis (RA), lupus, vasculitis, cystic fibrosis (CF) etc. Specifically, neutrophil extracellular trap (NET) formation has been identified as a link between innate and adaptive immune responses in autoimmunity. Autoantigens including neutrophil granular proteins (targeted by anti-neutrophil cytoplasmic antibodies, ANCA) as well as post-translationally modified proteins, i.e. citrullinated and carbamylated proteins targeted by anti-citrullinated protein antibodies (ACPA) and anti-carbamylated protein antibodies (ACarPA), respectively, localize to the NETs. Moreover, NETs provide stimuli to dendritic cells that potentiate adaptive autoimmune responses. However, while NETs promote inflammation and appear to induce humoral autoreactivity across autoimmune diseases, the antigen specificity of autoantibodies found in these disorders is striking. These unique autoantigen signatures suggest that not all NETs are created equal and that the environment in which NETs arise shapes their disease-specific character. In this review article, we discuss the effects of different stimuli on the mechanism of NET formation as well as how they contribute to antigen specificity in the breaking of immune tolerance. Specifically, we compare and contrast the autoreactive nature of NETs in two settings of chronic airway inflammation: one triggered by smoking, a recognized environmental NET stimulus in RA patients, and one mediated by Pseudomonas aeruginosa, the most prevalent lung pathogen in CF patients. Finally, we draw attention to novel findings that, together with the specific environmental/chemical stimuli, should be taken into account when investigating how and why antigen specificity arises in the context of NET formation. Highlights: Neutrophil extracellular traps (NETs) play an important role in the development of autoimmunity. Differential stimulation of NETs influences autoantigen specificity in chronic inflammatory diseases. NETs in smokers' lungs are associated with autoantibodies to citrullinated proteins in rheumatoid arthritis patients. Pseudomonas-aeruginosa triggered NETs provide a model for the development of autoimmunity in cystic fibrosis patients.